2012
DOI: 10.1186/1477-7819-10-240
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma of the jaws: a review of literature and a case report on synchronous multicentric osteosarcomas

Abstract: BackgroundIn the head and neck region, osteosarcoma is the most common primary malignant bone tumor, representing 23% of total head and neck malignancies. Osteosarcomas of the jaws are nevertheless rare lesions, representing only 2 to 10% of all osteosarcomas. This report reviews a single-center histopathology experience with craniofacial osteosarcomas, and reports the management of unusually large synchronous mandibular and maxillary osteosarcomas in a patient.Patients and methodsA search of the hospital path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 31 publications
2
45
0
1
Order By: Relevance
“…On the contrary, Alishahi et al, 13 Adebayo et al, 19 and Chindia et al 20 reported male predominance. The difference between male and female reported in these studies is, however, marginal; the mean age of occurrence of osteosarcoma in this series was concurrent with most reports from different literature; 12,13,18,26 however, it did not coincide with the mean age reported by Adebayo et al 19 Rhabdomyosarcoma, a malignancy of primitive muscle, predominates in pediatric patients in the first decade of life, making it the most common maxillofacial sarcoma in childhood but can be seen at any age. 18,27 In this study, rhabdomyosarcoma was the third most common sarcoma accounting for 9.7%.…”
Section: Discussionsupporting
confidence: 77%
“…On the contrary, Alishahi et al, 13 Adebayo et al, 19 and Chindia et al 20 reported male predominance. The difference between male and female reported in these studies is, however, marginal; the mean age of occurrence of osteosarcoma in this series was concurrent with most reports from different literature; 12,13,18,26 however, it did not coincide with the mean age reported by Adebayo et al 19 Rhabdomyosarcoma, a malignancy of primitive muscle, predominates in pediatric patients in the first decade of life, making it the most common maxillofacial sarcoma in childhood but can be seen at any age. 18,27 In this study, rhabdomyosarcoma was the third most common sarcoma accounting for 9.7%.…”
Section: Discussionsupporting
confidence: 77%
“…24 Although rare in jawbone locations, 25-27 diagnosis of low-grade osteosarcoma should be considered in the context of fibro-osseous lesions due to its specific management. 28,29 Overexpression and gene amplification of MDM2 in low-grade/dedifferentiated osteosarcomas, linked to supernumerary ring 12q13-15 chromosomes containing MDM2, 22,30 have together been proven to be a sensitive and specific diagnostic tool for these tumors in extragnathic locations. Unlike fibrous dysplasia and low-grade osteosarcoma, no recurrent genetic abnormalities have been reported for ossifying fibroma, which remains a lesion of uncertain nature, arising from the periodontal ligament.…”
Section: Discussionmentioning
confidence: 99%
“…It is the most common primary tumor of malignant bone tumors (1). Osteosarcoma may occur at any age, though has been most frequently observed in adolescents <25 years old, and is considered to occur more often in males than females (3).…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma is a malignant primary tumor of the bone, which can produce a bone-like tumor comprised of bone connective tissues, including collagen, elastic fibers and ground substances (1,2). It is the most common primary tumor of malignant bone tumors (1).…”
Section: Introductionmentioning
confidence: 99%